The Spanish legal regime for the import of cultural goods after the entry into force of Regulation 2019/880 and the implementation of the electronic system for its management on June 28, 2025 - Bergel Sainz de Baranda, Yolanda (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
On June 28, 2025 the centralised electronic system for the management of the new uniform European regime for the introduction and import of cultural goods established in Regulation (EU) 2019/880 starts operating. The functioning of this system makes such Regulation and the licences and statements system established in it fully effective. In this manner, the control of entry of cultural goods at the borders of the EU is reinforced to impede the introduction and import of goods unlawfully exported from third countries, avoiding possible damages to the goods and the financing of illicit activities through the sale of such goods to buyers in the EU. In this article we study this new regulation and its application through the centralised electronic system.